Synthesis and Biological Activity of Some 3-[(4-Amino-5-thioxo-1,2,4-triazol-3-yl)methyl]benzothiazol-2(3H)-one Derivatives - Dundar, Yasemin; Kaynak Onurdag, Fatma; Önkol, Tijen (Asian Journal of Chemistry, 2012)
Fourteen new 3-[(4-amino-5-thioxo-1,2,4-triazol-3-yl)methyl]benzothiazol-2(3H)-one derivatives have been synthesized. The structures of these compounds were confirmed by IR, 1H NMR, mass spectrum and elemental analysis. The synthesized compounds were evaluated for their antibacterial activity against various gram-positive and gram-negative strains of bacteria and their clinical isolates, for their antifungal activity against Candida albicans and C. krusei and for their antimycobacterial activity against M. tuberculosis H37Rv and its clinical isolate. Some of the compounds showed promising activity.